2021
DOI: 10.3390/ijms22041888
|View full text |Cite
|
Sign up to set email alerts
|

Loliolide, a New Therapeutic Option for Neurological Diseases? In Vitro Neuroprotective and Anti-Inflammatory Activities of a Monoterpenoid Lactone Isolated from Codium tomentosum

Abstract: Parkinsons Disease (PD) is the second most common neurodegenerative disease worldwide, and is characterized by a progressive degeneration of dopaminergic neurons. Without an effective treatment, it is crucial to find new therapeutic options to fight the neurodegenerative process, which may arise from marine resources. Accordingly, the goal of the present work was to evaluate the ability of the monoterpenoid lactone Loliolide, isolated from the green seaweed Codium tomentosum, to prevent neurological cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…The monoterpene lactone, loliolide which was identi ed in both TRDF and TREF was recently described as a potent anti-in ammatory and neuroprotective metabolite (Silva et al, 2021). Similarly, aesculetin and several other coumarins derivatives are well known anti-in ammatory agents (Grover & Jachak, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The monoterpene lactone, loliolide which was identi ed in both TRDF and TREF was recently described as a potent anti-in ammatory and neuroprotective metabolite (Silva et al, 2021). Similarly, aesculetin and several other coumarins derivatives are well known anti-in ammatory agents (Grover & Jachak, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of Lut7 was evaluated by the means of different methodologies, namely (a) 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging ability [ 19 ]; (b) oxygen radical absorbance capacity (ORAC) [ 20 ]; and (c) ferric reducing antioxidant power (FRAP) assays [ 21 ] with slight adaptations [ 15 ]. Butylated hydroxytoluene (BHT) was used as a positive control for antioxidant activity.…”
Section: Methodsmentioning
confidence: 99%
“…Its potential benefits to the CNS include the decrease of microglia activation and neuronal protection [ 3 , 4 , 5 ]. However, the glycosylated form of luteolin, known as cyranoside or luteolin-7-O-glucoside (Lut7) (PubChem ID 5280637), was reported as a selective JNK3 inhibitor, five times more selective than luteolin [ 6 ], which plays a key role in neurodegenerative diseases [ 7 , 8 , 9 , 10 , 11 ], suggesting that patients with neurodegenerative diseases might benefit from a natural or bio-inspired product-based therapy [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Monoterpenoid lactone loliolide was identified in both extracts. Loliolide was previously isolated from different seaweeds, such as Codium tomentosum [43], Sargassum horneri [44], and Undaria pinnatifida [45]. It is considered to possess antioxidant and anticancer activity.…”
Section: Isoamijiolmentioning
confidence: 99%
“…It is considered to possess antioxidant and anticancer activity. In addition, it is suggested that loliolide could be applied in the development of new neuroprotective therapeutics for Parkinson's disease, due to its antioxidant, anti-inflammatory, and neuroprotective mechanisms [43]. Moreover, among representatives of terpenoids, isoamijiol and isoamijiol oxidation products were identified.…”
Section: Isoamijiolmentioning
confidence: 99%